(untitled) (Research, Society and Development, 2019)
The History of Mathematics Education (HEM) has been consolidating in the last decades as a promising field of research, with the purpose of examining the teaching and learning processes of Mathematics, making a dialogue between the present time and the other generations. One of the research categories of this area of study is the analysis of school notebooks. In this context, the present work aims to discuss the potential of historical studies using schoolbooks as a source of research. In addition, we intend to investigate the pedagogical practices used by teachers of Mathematics, from personal schoolbooks used in the Final Years of Elementary School, in the Municipal School Professor Terezinha Paulino de Lima, located in Natal, Rio Grande do Norte, between the years of 2002 and 2005. For this, the methodological course consisted in investigating in the literature how schoolbooks constitute an important source of information. We also analyzed the notes made in four books with mathematics classes from the same student in different school years in order to make a contribution to the historical reconstruction of mathematics teaching and to constitute important physical archives for HEM in Rio Grande do Norte. It was noticeable in this investigation that there is a close relationship between the annotations of the mathematics classes expressed in the school notebooks with the propagation of the mathematical knowledge. Therefore, it is possible to conclude that this resource constitutes an important source of information to better understand the universe of Education. This approach gains strength as a methodological strategy, in the field of HEM, allowing the (re) organization of historiographic sources, from the main protagonist of this process: the subject.